Utilization of Intravenous Ribavirin Among Reproductive Age Adults in 2010–2017: A Population-Based Study in the Yinzhou District, Ningbo City of China - Li, Hailong; Zhao, Houyu; Lin, Hongbo; Shen, Peng; Liu, Cuili; Zhan, Siyan (Frontiers in Public Health, 2021)
Background: Intravenous (IV) ribavirin is not approved in US and European Union, but it is authorized in China. Significant teratogenic and embryocidal effects of ribavirin have been found in almost all animal studies, it is critical to investigate the prevalence and trends of the utilization of IV ribavirin among reproductive age population. Objective: To evaluate the prevalence and trends of IV ribavirin use among reproductive-age population in 2010-2017. Methods: The study design of our study is retrospective cross-sectional study based on healthcare database. We identified and extracted the data of residents aged 18 to 44 years by using Yinzhou database at 21 January, 2018. A cohort of IV ribavirin users were identified through outpatient prescription records in 3 general hospitals and 24 community health centers from 2010 to 2017. We reported the number, proportion, and prevalence of the exposure to IV ribavirin stratified by sex, age, marital status, education level, occupation, hospital level, calendar year, diagnosis, and dosage. The overall trends of IV ribavirin use, and the trends in different levels of hospital and common diagnoses were further analyzed and described. Result: During the study period, the prevalence of IV ribavirin use among reproductive-age adults was 6.02% (48,287/801,667). Relatively higher prevalence were found in adults aged 40-44 (8.04%, 95%CI: 7.90 – 8.17), unmarried patients (8.91%, 95%CI: 8.74 – 9.08), and who had more than 9 years of education (6.82%, 95%CI: 6.74 –6.90). Compared to secondary and tertiary hospitals, IV ribavirin was more likely to be dispensed in primary hospitals (19.44%, 95%CI: 19.28 – 19.61). The most common diagnoses were acute upper respiratory infections (AURIs), accounting for 80% of the patients exposed to IV ribavirin. For patients with AURIs, the prevalence of IV ribavirin was nearly 30%. Overall, the prevalence of IV ribavirin use decreased from 1.72% in 2010 to 0.24% in 2017. Conclusion: We found IV ribavirin was mainly used for AURIs which suggested that a large amount of IV ribavirin use was probably inappropriate. The prevalence was decreasing by 87% over the past eight years, and we encourage clinicians and pharmacists to continually avoid inappropriate use of IV ribavirin.